Hemoptysis as an unusual manifestation of thoracic aortic aneurysm - Salazar-Flórez, Jenny Carolina (2020)
Aortic aneurysms correspond to a focal dilation of the artery wall that exceeds 50% of its normal diameter. Most cases correspond to the abdominal location, being a small proportion described at the level of the thoracic aorta. In this segment, less than 10% of patients experience symptoms and even rupture may constitute the first manifestation. It is presented an octogenarian woman with hemoptysis and hemodynamic instability in which the diagnosis of thoracic aortic aneurysm was made through contrasting angiotomography and then she receives a successfully endovascular management. Given the prognosis of this pathology, an adequate use of imaging studies is vital for a successful radiological diagnosis that allows for a timely therapeutic approach.